Yoga pada Anak untuk Meningkatkan Kemampuan Motorik dan Kognitif pada Anak Usia Prasekolah - Fransisca Desti Kurniasih; Isfaizah; Dona Rande Bua; Galih Ayu Tias; Adelina Maharani Tugestim; Binti Yuliana; Wahyuni; Fentisarti (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Preschoolers are children who are experiencing growth and development. Toddlerhood is an important period in the process of human growth and development. Toddlers are a general term for children aged 1-3 years (toddlers) and preschoolers (3-5 years). The early years of a child's development are the beginning of their long-term health and well-being. Early childhood gains cognitive, verbal, and social-emotional skills in the early years of life and their brains develop rapidly. Objective: The purpose of this yoga service for preschool children is to improve motor and cognitive abilities and develop emotional self-regulation skills in managing emotions, calmness and self-reflection and improve the focus and concentration of learning for preschool children with yoga education for children. Method: This community service was carried out simultaneously in three regions of Indonesia, including Vinsensius Pudak Payung Kindergarten Semarang with 11 students, Kemala Bhayangkari 02 Kindergarten Bulungan North Kalimantan with 9 students, Kemala Bhayangkari 09 Kindergarten Sangatta Utara East Kalimantan with 15 students, on June 3, 2025 at 08.00-09.00. This activity began with explaining and educating children about yoga, then continued with yoga practice. This activity was carried out by starting with warm-up movements, core movements and cooling movements. Results: after the education was carried out, the children understood the importance of yoga. The community service carried out in kindergarten went well and the children followed the yoga movements directed by the instructor enthusiastically. Conclusion and suggestions: children's yoga can improve concentration, learning cognitive abilities, and gross motor skills, as well as emotional intelligence and body balance in preschool children and it is hoped that teachers will do this yoga in ice breaking sessions during class hours to refresh children's brains.   Abstrak Anak  prasekolah  adalah  anak  yang  sedang  mengalami pertumbuhan dan perkembangan. Masa balita merupakanperiode penting dalam proses tumbuh kembang manusia.Balita  adalah  istilah  umum  bagi  anak  usia  1-3  tahun(batita)  dan  anak  prasekolah  (3-5  tahun). Pada tahun-tahun awal perkembangan anak merupakan awal bagi kesehatan dan kesejahteraan mereka dalam jangka panjang. Anak usia dini mendapatkan keterampilan kognitif, verbal, dan sosial-emosional pada tahun-tahun awal kehidupannya dan otak mereka berkembang dengan cepat. Tujuan: dari pengabdian yoga pada anak pra sekolah  ini adalah untuk Meningkatkan kemampuan motorik dan kognitif serta mengembangkan keterampilan emosional regulasi diri dalam mengelola emosi diri, ketenangan dan refleksi diri serta meningkatkan fokus dan konsentrasi belajar anak usia pra sekolah dengan edukasi yoga pada anak. Metode: pengabdian masyarakata ini di lakukan serentak di tiga wilayah indonesia yang meliputi TK Vinsensius Pudak Payung Semarang sebanyak 11 siswa,TK Kemala Bhayangkari 02 Bulungan Kalimantan Utara sebanyak 9 sisawa, TK Kemala Bhayangkari 09 Sangatta Utara Kalimantan Timur sebanyak 15 siswa, pada tanggal 03 Juni 2025 pukul 08.00-09.00. Kegiatan ini di mulai  dengan menjelaskan dan edukasi tetang yoga anak, kemudian di lanjutkan dengan praktek yoga. Dalam kegiatan ini di lakukan dengan di awali gerakan pemanasan, gerakan inti dan gerakan pendinginan. Hasil : Setelah di lakukan edukasi anak-anak paham tentang pentingnya yoga, Pengabdian yang di laukan di taman kanak-kanak berjalan dengan baik dan anak- anak mengikuti gerakan yoga yang di arahkan oleh instruktur dengan antusias. Kesimpulan dan saran : yoga anak mampu meningkatkan konsentrasi belajar kemampuan kognitif, dan kemampuan motorik kasar, serta kecerdasan emosional dan keseimbangantubuh pada anak usia prasekolah dan diharapkan guru melakukan yoga ini di sesi-sesi ice breaking jam pelajaran untuk merefresh otak anak.